Use of atypical antipsychotics in the treatment of schizophrenia in the Brazilian National Health System: a cohort study, 2008-2017 - Izabela Fulone; Marcus Tolentino Silva; Luciane Cruz Lopes (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to investigate sociodemographic and clinical characteristics of users of atypical antipsychotics receiving care via the Specialized Component of Pharmaceutical Assistance (Componente Especializado da Assistência Farmacêutica - CEAF), for the treatment of schizophrenia in Brazil, between 2008 and 2017. Methods: this was a retrospective cohort study using records of the authorizations for high complexity procedures retrieved from the Outpatient Information System of the Brazilian National Health System, from all Brazilian states. Results: of the 759,654 users, 50.5% were female, from the Southeast region (60.2%), diagnosed with paranoid schizophrenia (77.6%); it could be seen a higher prevalence of the use of risperidone (63.3%) among children/adolescents; olanzapine (34.0%) in adults; and quetiapine (47.4%) in older adults; about 40% of children/adolescents were in off-label use of antipsychotics according to age; adherence to CEAF was high (82%), and abandonment within six months was 24%. Conclusion: the findings expand knowledge about the sociodemographic and clinical profile of users and highlight the practice of off-label use.